PERANCANGAN SISTEM INFORMASI PERSEDIAAN WASTE DI PT. KEWALRAM INDONESIA UNIT 2 SUMEDANG - Denta Lidia Hera Kusuma; Encep Supriatna (Ma'soem University, 2018)
Results of research conducted at PT. Kewalram Indonesia Unit-2, in its data processing, still using manual system that is in data of waste inventory using register book, so very susceptible to keruskan and data loss, not optimal in making report because herus recapture from receipt book, and waste expenditure, difficulty in search stock waste.Metode used in this research is System Development Methods are methods, procedures, work concepts, rules and postulates (postulates) that will be used to develop an information system. As for system design manggunakan Development Life Cycle System (SDLC) with Waterfall method is a method used to help and facilitate the development of the system. Waste Inventory Information System Design is built using Microsoft Visual Foxpro 9.0 and foxpro database. Thus the system of the author of the design is expected to improve data security from the possibility of data loss and data damage, facilitate the making of Reports, as well as simplify the search for waste inventory waste.